2009
DOI: 10.1111/j.1551-2916.2008.02848.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Creep Behavior of a Si3N4–SiC Micronanocomposite

Abstract: The microstructure and its influence on the creep behaviour of carbon derived Si3N4‐SiC micro/nanocomposite tested in bending at temperatures from 1200° to 1400°C in air has been studied. No phase and microstructure change after creep test implied that material is stable at tested temperature range. After creep test only partial crystallization of glassy intergranular phase has been observed. Creep parameters n close to 1, apparent activation energy around 350 kJ/mol together with TEM observation indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Kagiarova et al [19] stated that the low value of the stress exponent is consistent with samples with low cavity concentration. According to the morphology of the investigated samples, the porosity increases by increasing copper and germanium concentration; accordingly the exponent stress factor would be increased too.…”
Section: Creep Behaviormentioning
confidence: 73%
“…Kagiarova et al [19] stated that the low value of the stress exponent is consistent with samples with low cavity concentration. According to the morphology of the investigated samples, the porosity increases by increasing copper and germanium concentration; accordingly the exponent stress factor would be increased too.…”
Section: Creep Behaviormentioning
confidence: 73%
“…As the best structural ceramics, SiC and Si 3 N 4 have been developed for decades and continue to be extended further . Specifically the SiC/Si 3 N 4 composites are of increasing interest because they should complement each other in the mechanical properties. With the sintering requirement of SiC/Si 3 N 4 composites the study of the phase relations at high temperature in SiC–Si 3 N 4 ceramic systems should be concerned.…”
Section: Introductionmentioning
confidence: 99%
“…The self‐diffusion coefficient of Si and C, also Si and N, is too low to get the fully dense ceramics without sintering aids. Rare‐earth oxides are often used as sintering aids for densification of SiC ceramics and SiC/Si 3 N 4 composites . In the present work rare‐earth oxides R 2 O 3 (R = La,Gd,Y) were chosen as the members of systems and they stand for La, typical light rare earth; Gd, medium rare earth; and Y, the representative heavy one with the similar property of other heavy rare earths, all of which typically generate a complete series.…”
Section: Introductionmentioning
confidence: 99%
“…Many researches have shown that SiC grains have an inhibitory effect on the secondary recrystallization of Si 3 N 4 grains and the inhibition effect increases with the increase of the size [9,11]. Therefore, the β-Si 3 N 4 grains would not grow too large to reduce the strength of materials.…”
Section: Tem Analysismentioning
confidence: 99%